The relationship between sources of knowledge and knowledge creation / Khalid Abdul Wahid, Mohd Nasir Ismail, Sawat Wanarat and Tipparat Laohavichien - Ismail, Mohd Nasir; Wanarat, Sawat; Laohavichien, Tipparat; Abdul Wahid, Khalid (Faculty of Information Management, 2013)
Knowledge-based economy is a new form of global economy in the 21st century. The term “knowledge-based economy” resulted from the recognition of the role of knowledge and technology in economic growth. In knowledge-based economy, continuous innovation is the key to sustainable competitive advantage. Innovation can strengthen the sustainable growth and productivity of a country and increase national productivity as well in the global market through creation of new ideas and opportunities. Innovation is extremely dependent on the availability of knowledge and therefore the complexity created by the explosion of richness and reach of knowledge has to be identified and managed to ensure successful innovation. This study investigates the relationship of sources of knowledge and knowledge creation among electrical companies located in Bangkok and the surrounding provinces. The findings show that there is a direct relationship between organization’s knowledge and knowledge creation as well as between organizational capability and knowledge creation. However, the study shows that there is no a relationship between market knowledge and knowledge.